ROMANS: PAUL'S PURPOSE AND AUDIENCE WITH SPECIAL ATTENTION TO ROMANS 9-11 - Guerra, Anthony J. (Revue biblique, 1990)
This article calls into question the widespread view among commentators on Romans that Paul is addressing primarily if not exclusively Gentile Christians and at most only incidentally Jewish Christians in Rome. The emphasis on the promises to the forefathers, the "seed of David", the exceptional recourse to scriptural warrants and most especially the content and mode of argumentation of Romans 9-11 contradict this consensus opinion. In addition to defending his gospel as consonant with Jewish Scripture and traditions, Paul also seeks to allay fears that his presence in Rome will enhance antagonism within the mixed Christian community and thus jeopardize the precarious relationship between Christians and the governing authorities. By arguing in this twofold way, Paul hopes to win the support of Gentile as well as Jewish Christians in Rome for his planned mission to the West. Cet article relance le débat au sujet de la thèse largement répandue chez les commentateurs de l'épître aux Romains, que Paul s'adresse en premier lieu, voire exclusivement, aux Chrétiens d'origine païenne et pour le mieux seulement incidemment aux Chrétiens d'origine juive habitant à Rome. La mise en valeur des promesses adressées aux Pères, la « semence » de David, le recours exceptionnel aux garanties scripturaires et tout spécialement le contenu et le mode d'argumentation de Rm 9-11 contredisent ce consensus. En plus de défendre le fait que son évangile est en accord avec les Écritures et les traditions juives, Paul cherche aussi à écarter les craintes que sa présence à Rome avivera l'antagonisme entre les diverses parties de la communauté chrétienne et de plus mettra en péril la relation précaire entre Chrétiens et autorités en exercice. En argumentant dans ces deux sens, Paul espère gagner l'appui des Chrétiens romains d'origine païenne aussi bien que ceux d'origine juive, en vue de la réalisation de sa mission vers l'ouest.